Prarancangan Pabrik Isobutilena dari Tersier Butil Alkohol dengan Proses Dehidrasi menggunakan Katalis Styrene-Divinylbenzene Kapasitas Produksi 25.000 Ton/Tahun - Ilmawati, Hanifia, M. Mujiburohman, S.T., M.T., Ph.D, Ir. Herry Purnama, M.T., Ph.D (2016)
Isobutylene or 2-methyl propene has a C4H8 molecule's formula. It's function for raw material producing methyl tersier butyl ether (MTBE) and ethyl tersier butyl ether (ETBE), that used to increase fuel's octane number. Isobutylene polymerization can produce butyl rubber. Reaction of isobutylene and phenol will produce antioxidant like butylated hydroxytoluene (BHT) and butylated hydroxyanisole (BHA). The manufacture of isobutylene through tersier butyl alcohols dehydration process helped by styrene-divinylbenzene catalysts in Continuous Stirred Tank Reactor (CSTR). The reaction takes place in endothermic, reversible, isothermal, at temperature 93oC and pressure 5 atm continuously. The raw material's needed of tersier butyl alcohols as much as 4,944.374 kg/hours and catalysts as much as 639.83 kg. This plant designed with a capacity 3,156.566 kg/hours. To support the production process, the supporting unit or utilities is needed to establish comprising a unit of water supply from processing river water as much as 8,278.309 kg/hours, the saturated steam needed as much as 8,297.806 kg/hours, the electricity supplied by PLN and generator set as much as 400 kW, the compressed air needed as much as 33.980 m3/hours and the needs of fuels as much as 418.571 L/hours. From the economic analysis conducted to this plant design with a fixed capital investment as much as IDR 552,631,138,816 and the working capital investment as much as IDR 410,041,015,688, it obtains return of investment (ROI) before tax as much as 41.85% and after tax as much as 29.29%. Meanwhile, pay out time (POT) before and after tax are 1.93 years and 2.54 years. Break even point and shut down point are as much as 43.56% and 27.38%. For discounted cash flow (DCF) as much as 30.11%. Based on the calculation of the economic analysis, it can concluded that this plant is reasonable to establish.